Isolation and Characterization of the Physiochemical Properties of Brewer’s Spent Grain - Kalidas Mainali; Madhav P. Yadav; Brajendra K. Sharma; Majher I. Sarker; Helen Ngo; Arland Hotchkiss; Stefanie Simon (Agriculture)
Large quantities of brewer’s spent grains are not fully utilized even as cattle feed. These feedstocks can be used to produce highly functional biomaterials, carbonaceous materials, and additives. In this investigation, four major fractions were isolated and characterized: Hemicellulose A, Hemicellulose B, cellulosic-rich fraction (CRF), and oligosaccharides. Overall, 21.4% Hemicellulose A, 18.5% Hemicellulose B, 17.4% cellulosic rich fraction, and 5.5% pure oligosaccharides were obtained from the hexane-extracted brewery’s spent grains. Detailed physio-chemical analyses of each fraction showed that these fractions can be used to produce useful products such as emulsifiers, carbonaceous materials, modified cellulosic fibers, additives, as well as N-doped chars. Component analyses revealed that, Hemi. A contains high fixed carbon (20 wt.%), followed by hexane extracted material (17.1 wt.%), CRF (14.6 wt.%), and Hemi. B (14.5%). Standard proximate analyses showed that Hemi. A has the highest protein (66 wt.%), which can be utilized as a renewable solid-state N-precursor as dopants during the thermochemical conversion process. The sugar composition revealed that BSG has a typical arabinoxylan structure with a high percentage of arabinose and xylose. It also contains a high percentage of glucose, which may come from the residual β-glucan present in the BSG. FTIR analyses revealed changes in the structure of each fraction. Hence, BSG and extracted fractions exhibit significant potential for waste valorization, contributing significantly to the full utilization of products from the brewing industry.